UPAYA PENINGKATAN KESADARAN PRILAKU HIDUP BERSIH DAN SEHAT PADA ANAK USIA SEKOLAH (SD) - Solikah, Siti Nur (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Health development aims to improve the degree of public health. The degree of public health is determined by behavioral factors. To support efforts to improve healthy behaviors, the national vision of health promotion is "Clean and Healthy Behavior (PHBS)." The child is our hope for the future. Adverse community behavior or lifestyles that can damage the public order in the health sector, can start from the behavior of individuals, families or the behaviors of society and school-age children. The purpose of this activity is to know the effect of health education on awareness, knowledge of PHBS and skills about hand washing and correct way of brushing. Based on observations found 60% of students seen snack in the open and using food preservatives, 75.5% of students did not wash hands before and after meals, 62.2% of students experienced dental caries as much as 67.7% of students frequent diarrhea as much as 58% and 54.8% of students are long and dirty nails. Lack of awareness of clean life behavior in elementary school age children is due to lack of socialization about the importance of clean living in school by health workers. Health education activities conducted on May 14, 2016, appropriate and targeted goals are school age students in Elementary School 2, Tugu, Jumantono Karanganyar with health education methods with lecture and demonstration techniques. After this activity is expected to increase student awareness level about PHBS in school.??